THE ENVIRONMENTAL CONTEXT AND THE CHILD DEVELOPMENT: BRAZILIAN STUDIES - Rosane Luzia de Souza Morais; Alysson Massote Carvalho; Lívia de Castro Magalhães (Journal of Physical Education)
ABSTRACT The objective of this study was to make an integrative review of the brazilian studies regarding the influence of environmental factors on global, cognitive and motor development. We searched for scientific articles in SciELO and MEDLINE from 2004 to 2014 using the key words "child development" "environment" and "Brazil." According to the established criteria for inclusion and exclusion, 38 studies were selected. The studies were conducted in different regions of Brazil using techniques that varied from screening to diagnostic tests. Most studies were related to risk factors or prevalence of delays. Those studies that focused on the influence of environmental quality on child development, either analyzed the family or the day care centers. We concluded that important literature for the foundation of intervention studies. Furthermore, there is a need for studies that analyze the dynamic interrelation between the environments experienced by the child and their influence on development.